Morphological characteristics and texture properties of chiffon cake incorporated with different particle size of young corn powder - Sia, Anna Pek Yin (Universiti Sains Malaysia, 2015)
Normally, dietary fiber-enriched bakery products have a less desired harder texture. The effects of different particles size (45, 125 and 250 µm) of YCP added into chiffon cake on the morphological characteristics and textural properties as well as the sensory attributes were investigated in attempt to improve the texture, thus the final quality of chiffon cake. The morphological characteristics and functional properties of the wheat flour and its composite with various YCP particles size were also studied. The composite flour with 45 µm YCP clumped more easily after hydration and become flaky. On the contrary, 250 µm YCP did not get hydrated well. The water holding capacity was increased with YCP addition and increased in YCP particles size while the oil holding capacity increased with decreased YCP particles size. Morphological differences were observed between the cake samples. The chiffon cake incorporated with 125 µm YCP showed a finer structure thin filaments connecting to adjacent cell as compared to chiffon cake incorporated with 45 and 250 µm YCP. Chiffon cake incorporated with 45 µm YCP showed coarser crumb morphology, more loosed structure, larger and irregular air cell sizes distribution as compared to morphology of chiffon cake prepared with 125 µm YCP. The additional of different particle size of YCP into the chiffon cake did not show any predicted trend exhibited by all textural attributes of the chiffon cakes. The textural profile analysis revealed that the chiffon cake incorporated with 45 µm YCP has the greatest hardness. Addition of 45 µm YCP also resulted in the highest chewiness and gumminess among all the chiffon cake samples. Chiffon cake prepared with 125 µm YCP remains the more desired choice in term of hardness. Meanwhile, all textural attributes of chiffon cake does not differ significantly from each other. Apart from that, results of sensory evaluation indicated that chiffon cake formulated by the incorporation of 250 µm YCP score the highest value for all sensory attributes except for the colour. Meanwhile, the chiffon cake formulated by using 45 µm YCP score the lowest in most of the sensory attributes except for texture and springiness. In a nutshell, incorporating YCP of similar particle size to the wheat flour or increasing slightly the particle size of the YCP may be recommended as the ideal particle size for preparing a fibre-rich, low GI index YCP supplemented chiffon cake without jeopardizing the textural properties and the sensory attributes of the products.